2018
DOI: 10.1002/lary.27190
|View full text |Cite
|
Sign up to set email alerts
|

Post‐acute care use after major head and neck oncologic surgery with microvascular reconstruction

Abstract: Level 2c. Laryngoscope, 2532-2538, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
34
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(43 citation statements)
references
References 33 publications
(67 reference statements)
7
34
2
Order By: Relevance
“…No previous studies had reported on insurance status or family support in this population. Our finding that prolonged hospitalization was a risk factor was also shown by Parhar et al and Hatcher et al 11,13 While tracheostomy was revealed to be an independent risk factor in the current study, Cramer et al did not find a significant difference in the need for post–acute care in patients with tracheostomies at discharge. 10 Increasing age was also an independent risk factor for post–acute care in this population.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…No previous studies had reported on insurance status or family support in this population. Our finding that prolonged hospitalization was a risk factor was also shown by Parhar et al and Hatcher et al 11,13 While tracheostomy was revealed to be an independent risk factor in the current study, Cramer et al did not find a significant difference in the need for post–acute care in patients with tracheostomies at discharge. 10 Increasing age was also an independent risk factor for post–acute care in this population.…”
Section: Discussionsupporting
confidence: 84%
“…13 Patients in the aforementioned studies also had reconstruction of a wide variety of head and neck defects. 10,11,13 Thus, we sought to identify demographic, perioperative, and social factors that independently predict the need for post–acute care in a cohort of patients undergoing free tissue transfer to reconstruct defects involving the oral cavity. Identifying patients who may need post–acute care may help with earlier discharge planning to reduce hospital length of stay and in counseling the patient and family about likely postoperative care needs.…”
mentioning
confidence: 99%
“…5 Nearly one-third of our cohort were discharged to PACFs. This matches the rate previously reported for microvascular reconstruction after major head and neck surgery by Cramer et al 5 (33.6%) but is elevated compared to that of Parhar et al 6 (15.8%) and Hatcher et al 7 (14.2%). Cramer et al 5 and Parhar et al 6 analyzed the National Surgical Quality Improvement Program (NSQIP) database, which included nonacademic, nontertiary referral hospitals that may serve a healthier patient population.…”
Section: Discussionsupporting
confidence: 90%
“…2,3 Since 2012, PACFs have accounted for about $41 billion in annual Medicare fee-for-service expenditures. 4 Patients undergoing major head and neck surgery are large contributors to these costs, as 14% to 16% are discharged to PACFs 5-7 for continued occupational, physical, and speech-language therapies. 8-10 Some factors that contribute to this disposition include age, functionality, comorbidities, available social support in the home setting, length of hospital stay, postoperative complications, and frailty.…”
mentioning
confidence: 99%
See 1 more Smart Citation